Podobarska delavnica Andreja in Ivana Cesarja v Mozirju od 1853 do 1936 - Markovčič, Maruška (Etnolog. Nova vrsta (Ljubljana), 1998)
The article presents the woodcarving workshop of Andrej and Ivan Cerar in Mozirje - one of the biggest woodcarving workshops in Slovenia in the latter half of the 19th and the first half of the 20th century. It provides a survey of the workshop's development, the production and sales procedures, the division of labour, the relationship between the employees and their master and the attitude of the environment towards the employees in the woodcarving'strade.
Keywords: Cerar, Andrej, 1824-1885; Cerar, Ivan, 1864-1936; ethnology; etnologija; rezbarstvo; rezbarske delavnice; Slovenia; Slovenija; 19./20. st.; zgodovinski pregledi